Manganese oxide nanoparticles supported on graphene oxide as an efficient nanocatalyst for the synthesis of 1, 2, 4‐oxadiazoles from aldehydes. (26th June 2020) - Saadati, Fariba; Kaboudin, Babak; Hasanloei, Rana; Namazifar, Zeinab; Marset, Xavier; Guillena, Gabriela
Abstract : The easy synthesis of graphene oxide (GO)‐supported manganese dioxide (MnO2 ) nanoparticles as a stable heterogeneous nanocatalyst (MnO2 @GO) is described. This catalyst was investigated in the synthesis of 1, 2, 4‐oxadiazoles from amidoximes and aldehydes via a cyclization and oxidation process. The nanocomposite was prepared and characterized using various techniques. The catalytic application of the nanocomposite was examined in the reaction of a variety of aldehydes with aliphatic and aromatic amidoximes. The stable and robust catalyst was recycled for seven consecutive runs without a significant decrease in the catalytic activity. Abstract : Graphene oxide (GO)‐supported manganese dioxide (MnO2 ) nanoparticles as a stable heterogeneous nanocatalyst (MnO2 @GO) were synthesized. The catalytic activity was examined in the synthesis of 1, 2, 4‐oxadiazoles from amidoximes and aldehydes via a cyclization and oxidation process.